Extremist Legitimate Defense in Iran's Criminal Proceedings (with an Emphasis on Intentional Homicide) - Saeed Ghaedi (پژوهشهای حقوقی)
The Islamic Penal Code of 1392, with its late entry into comply, has accepted extreme or excessive legitimate defense and developed legitimate defense. From the point of view of the new legislator, the Imperfect legitimate defender on the other hand, and is not the same as someone who in an aggressive and oppressive manner, he commits another murder, and on the other hand, in intentional murder, he deserves to be decriminalized from the punishment of retribution without absolute decriminalization. Despite this, it is recommended to consider Note 2 of Article 156 and Note 2 of Article 302, the need for a logical interpretation in determining the rule. The acceptance of legitimate defense requires an extreme, even though in this decision, both the conditions of defense and the degree of defense have been taken into account. The current research, using the analytical-descriptive method and collecting the required information in the library method, and relying on the cases of intentional homicide in the criminal justice system, Iran tries to evaluate the impact and impression of the judicial procedure of legal duality with the approaches of punishment based on defense conditions. and show the levels of defense, and at the end, while emphasizing the need for consistent criminal policy in order to protect the rights of walid the conclusion is reached that Note 2 of Article 302 is only about crimes and is based on non-observance of the levels of defense despite the necessity and truth of the principle of defense And the position of Note 2 of Article 156 also applies to other crimes in the absence of one of the conditions of legitimate defense .The effect of extreme legitimate defense in crimes is the deliberate impunity of revenge, and in other crimes, it is simply the imposition of the burden of the lack of defense conditions on the defender from the attacker.